Cash-flow sensitivities and the allocation of internal cash flow - Chang, Xin (2015)
We study how firms allocate cash flow by estimating the cash-flow sensitivities of various uses of cash flow. We decompose cash flow into a transitory and a permanent component and focus on the allocation of the transitory component, which by construction contains little information about future growth opportunities. We find that more financially constrained firms allocate more transitory cash flow to cash savings and direct less toward investment than do less constrained firms, consistent with constrained firms accumulating liquidity to buffer against future financial constraints. We also illustrate several methodological advantages of our approach over alternative methods in previous studies.